The Character Formation of Children in Japan: A Study of Japanese Children Textbook on Moral Education (Doutoku) - Linda Unsriana; Rosita Ningrum (Bina Nusantara University, 2018)
The purpose of this research was to explore any underlying messages or moral principle in Japanese elementary school textbook titled “Watashitachi no Doutoku” and its correlation with the character formation of children in Japan. The method used in this research was the literature review that was derived from corpus data in the form of an original Japanese manuscript. The corpus data were derived from textbooks that were still being used in Japan to date, in the form of original books in the Japanese language from the first grade to sixth grade elementary school, whereas the research method used a descriptive analysis method. The problem analysis was divided into four sections, including intrapersonal morality, interpersonal moral value, morality toward nature, and morality toward society. The conclusion indicates that character installment through special school subjects, namely moral education (doutoku), using Watashitachi no Doutoku influences character formation of elementary school children in Japan.